Pengaruh Profesionalisme Waiter Dan Waitress Terhadap Keberhasilan perasional Food And Beverge Service Di Riss Hotel Malioboro Yogyakarta - I Ketut Suardana Ketut; Netty Rosita Pandiangan (JURNAL NUSANTARA, 2025)
This final project report entitled “The Influence of Waiter and Waitress Profeesionalism on the succes of Food and Beverage Service operations at Riss Hotel Malioboro Yogyakarta”. The succes of food and beverage service in the hospitality industry is greatly influenced by the profesionalism of waiter and waiterss in serving guest. This study aims to know the extent to which the profesionalism of food and beverage service staff has an impact on the level of guest satisfaction and the operational succes of Riss Hotel Malioboro Yogyakarta. The purpose of this final project is to determine the effect of profesionalism of waiter and waiterss on the succes of food and beverage service operations at Riss Hotel Malioboro Yogyakarta. The research method use is descriptive qualitative with data collection techniques throught observation, documentation and interviews with hotel guest and staf food and beverage service at the hotel. Aspect of profesionalism analyzed include product knowledge, communication skills, serve attitude, and speed and accuracy in serving guest. The result showed that the higher the profesionalism of waiter and waiterss,the more positive the guest experience in enjoying food and beverage service at the hotel. The main factors that contribute to the succes of food and beverage services are interpersonel skills, the ability to understand guest needs, and the application of good operational stndarts.